Pedagogical management and teaching performance of Peruvian teachers in a vulnerable area of Lima - Figueroa Huamán, Marlene Genoveva (2023)
This article develops the pedagogical management of the headmaster and its link with teacher performance in a pandemic situation. The objective of the study was to analyze the relationship between the mentioned variables in an educational institution located in a highly vulnerable area of Lima - Peru. The sample consisted of 54 teachers at the primary and secondary levels, who provided data from questionnaires validated for this research. The variables were evaluated using Spearman's Rho correlational coefficient for the three dimensions that justify pedagogical management and teacher performance: I. Planning; II. Organization; III. Direction and control. The results revealed that there were positive and significant correlations between the variables mentioned.